Prospective of Curriculum Revision in Mechanical Engineering, Institute of Engineering Tribhuvan University - Shrestha, Rajendra (Journal of Advanced College of Engineering and Management, 2018)
Continuous revision of curriculum is important in academic institutions. First revision of the curriculum of Mechanical Engineering was completed in 1999. Second revision of the curriculum was started in 2009 and completed in 2015. It is important for engineering practice to make competitive curriculum for producing quality students by using modern techniques, skills and engineering tools. Analysis of Curriculum-1999 and 2009 were performed. General out lines of the curriculum revisions were introduced. Features of the curriculum revisions were discussed in detail. Competitive analysis of curriculums of contemporize universities of Asia were performed. Accreditation process were analysed, taking reference of European and American systems. Updating equipment in workshop and laboratories with latest technologies were found necessary.